Pengaruh Media Video YouTube “Lapor Pak” terhadap Keterampilan Menulis Teks Anekdot pada Siswa Kelas X SMAN 6 Kediri Tahun Pelajaran 2023/20244 - Indria Rani, Evika; Pitoyo, Andri; Puspitoningrum, Encil (Efektor, 2024)
Writing skills are productive skills and are considered as skills that require more attention than other skills. In learning Indonesian, one of the texts that must be studied by high school students is anecdotal texts. An anecdote text is a story that aims to convey criticism or satire through jokes. In learning anecdotal text, the YouTube video "Lapor Pak" is considered to be able to improve students' writing skills, because the video contains a joke in the form of a satire related to the anecdote text. This type of research is quantitative research. Data collection used anecdotal text writing tests. The analysis technique used is the independent sample t-test with the prerequisite tests for normality and homogeneity. The research results showed that the class that received YouTube media treatment experienced an increase in test scores. This means that the YouTube video media "Report Pak Trans 7" affects students' writing skills. The results of the t-test for equality of means column show the value of t-count = 5.839 > t-table = 1.99085, so it can be used as a basis for decision-making in accepting the independent samples t-test research hypothesis with acceptance of H1 with the conclusion that there is a significant difference. Based on the results of this research, Indonesian language teachers should be able to utilize more creative and innovative learning media. Determining the right media can certainly have a positive impact on increasing student enthusiasm and curiosity during the learning process.